Strategic planning and organisational performance in health delivery service - a case-study of the Trust Hospital - Tetteh, Edward Ato (2012)
A Dissertation submitted to the Board of Post Graduate Studies,Kwame Nkrumah University of Science and Technology, Kumasi in partial fulfilment of the requirements for the award of Master of Arts in Industrial Management.